HDACs and Their Inhibitors on Post-Translational Modifications: The Regulation of Cardiovascular Disease - Siyi Yang; Yidong Sun; Wei Yu (Cells, 2025)
Cardiovascular diseases (CVD), such as myocardial hypertrophy, heart failure, atherosclerosis, and myocardial ischemia/reperfusion (I/R) injury, are among the major threats to human health worldwide. Post-translational modifications alter the function of proteins through dynamic chemical modification after synthesis. This mechanism not only plays an important role in maintaining homeostasis and plays a crucial role in maintaining normal cardiovascular function, but is also closely related to the pathological state of various diseases. Histone deacetylases (HDACs) play an important role in the epigenetic regulation of gene expression, and play important roles in post-translational modification by catalyzing the deacetylation of key lysine residues in nucleosomal histones, which are closely associated with the occurrence and development of cardiovascular diseases. Recent studies indicate that HDAC inhibitors (HDACis) may represent a new class of drugs for the treatment of cardiovascular diseases by influencing post-translational modifications. In this review, we systematically summarize the mechanism of action of HDACs and HDACis in post-translational modifications related to common cardiovascular diseases, providing new ideas for the treatment of CVD, and explore possible future research directions on the relationship between HDAC and HDACi in post-translational modifications and cardiovascular diseases.